Attitude and practice of cervical cancer screening among the female doctors of Bangabandhu Sheikh Mujib Medical University (Bangladesh Medical Journal, 2016)
Cervical cancer is the most common cancer in Bangladesh, in spite of having established screening program. This cross-sectional study was performedin Bangabandhu Sheikh Mujib Medical University (BSMMU) from July 2012- June2013 to determine the attitude and practice of cervical cancer screening among 401 female doctors of BSMMU. All the information was collected in a structured questionnaire and data were analyzed using SPSS version: 17.0. About 40.9% of female doctors had good knowledge regarding cervical cancer screening and 80.8percent of female doctors did not ever have a screening test. The less the participants age, poor knowledge score and participants having only graduate degree, the less was the practice of cervical cancer screening(P